Fecal Microbiota Transplantation Donor and Dietary Fiber Intervention Collectively Contribute to Gut Health in a Mouse Model - Zhong, Yifan; Cao, Jiahong; Ma, Yanfei; Zhang, Yu; Liu, Jianxin; Wang, Haifeng (Frontiers in Immunology, 2022)
Transforming the gut microbiota has turned into the most intriguing target for interventions in multiple gastrointestinal and non-gastrointestinal disorders. Fecal microbiota transplantation (FMT) is a therapeutic tool that administers feces collected from healthy donors into patients to help replenish the gut microbial balance. Considering the random donor selection, to maintain the optimal microbial ecosystem, post-FMT is critical for therapy outcomes but challenging. Aiming to study the interventions of different diets on recipients’ gut microbiota post-FMT that originated from donors with different diets, we performed FMT from domestic vs. wild pigs that are living on low-fiber vs. high-fiber diets into the pseudo-GF mouse, followed with fiber-free (FF) or fiber-rich (FR) diets post-FMT. Different patterns of gut microbiota and metabolites were observed when mice FMT from different donors were paired with different dietary fiber contents. Enrichment of bacteria, including Akkermansia and Parabacteroides, together with alteration of metabolites, including palmitic acid, stearic acid, and nicotinic acid, was noted to improve crypt length and mucus layer in the gut in mice FMT from wild pigs fed an FR diet. The results provide novel insight into the different responses of reconstructed gut microbiota by FMT to dietary fiber. Our study highlighted the importance of post-FMT precise dietary interventions.